Enhancing coherent energy transfer between quantum devices via a mediator - Alba Crescente; Dario Ferraro; Matteo Carrega; Maura Sassetti (Physical Review Research, 2022)
We investigate the coherent energy transfer between two quantum systems mediated by a quantum bus. In particular, we consider the energy-transfer process between two qubits and how it can be influenced by using a third qubit or photons in a resonant cavity as mediators. Inspecting different figures of merit and considering both on- and off-resonance configurations, we characterize the energy-transfer performances. We show that while the qubit-mediated transfer shows no advantages with respect to a direct-coupling case, the cavity-mediated one is progressively more and more efficient as function of the number of photons stored in the cavity that acts as a quantum bus. The speeding-up of the energy-transfer time, due to a quantum mediator, paves the way for new architecture designs in quantum technologies and energy-based quantum logics.